Pengaruh Pemberian Ibuprofen Preoperatif Terhadap Kepadatan Serabut Kolagen Pada Proses Penyembuhan Luka Pasca Ekstraksi - Noer Avila Firdauzi; Soemartono; Monika Elidasari (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2016)
Background: Socket healing after extraction have two phases the healing of soft tissue and hard tissue. Ibuprofen is one of the NSAID that act as well as analgesics and antiinflammatory drugs. Ibuprofen is generally used in dental clinics after extraction to relieveof pain after tooth extraction. Preoperative Ibuprofen take effect of density of collagen fibers in the proliferative phase. The formation of collagen fibers in the socket healing process is important to support the strength of the tissue. The collagen is initiated healing of soft tissue and begin process of bone healing. Purpose: The purpose of this research was to know the influence of preoperative Ibuprofen related to density of collagen fibers on the socket healing process after extraction. Materials and Methods: This research is true experimental laboratorium. The subjects of this research were 20 Wistar rats which are divided into a control group (K) and treatment group (X). The treatment group was given preoperative Ibuprofen 1 hour before the tooth extraction and the control group were given only 0.2% NaCMC. The Wistar rats were decapitated on day 7 and then the appearance of collagen density is seen histologically. The results were analyzed with statistical methods Mann Whitney test. Results: The results showed a significant difference between control group and treatment group (p <0.05). Conclusion: The preoperative Ibuprofen give less of collagen density on socket healing process after tooth extraction.